The guru in you : a personalized program for rejuvenating your body and soul : unlock the powers of health and healing within - Alborzian, Cameron (New York, NY : HarperOne, 2011)
Invites you to embark on a journey to reconnect with your body and discover its natural ability to heal. As a male supermodel, Cameron Alborzian had a life that many dream of--traveling the globe, working with prestigious designers, partying with celebrities, and appearing in major ad campaigns and cultural landmarks like Madonna's "Express Yourself" video. But his real achievement came when he decided to leave the material world of high fashion and investigate the ancient art of Ayurvedic healing. What he learned changed his life, and, after years of study, he now works with everyone from Hollywood celebrities to executives of international corporations to bring balance, improved health, and inner peace to their busy lives. The tools he provides for his clients are now available to all with this book.--From publisher description.
Pt. 1: The path. The material world ; Setting your intention : the first step toward happiness -- Pt. 2: Foundation. The practice of nonviolence : kindness toward ourselves and others ; The practice of detachment : allowing what nature intends for us ; Letting go of excess : knowing when enough is enough (or the perfect amount). Pt. 3: Expression. Posture practice and the pursuit of inner beauty ; The breath ; Living the Ayurveda way : three stories of three women ; Practices for building awareness -- Pt. 4: Union. Putting it all into practice.
Includes bibliographical references (p. [263]).
Keywords: Hatha yoga